Global self-esteem and coping with stress by Polish students during the COVID-19 pandemic - Kupcewicz, Ewa; Cybulska, Anna Maria; Schneider-Matyka, Daria; Jastrzębski, Paweł; Bentkowska, Aleksandra; Grochans, Elżbieta (Frontiers in Public Health, 2024)
Objectives: Students experience considerable stress and anxiety during the course of their studies, which has a significant impact on their health and hinders the learning process. There are many stressors that can intensify stress, which is why choosing the right strategies for coping with stress and self-esteem is so important. Methods: The study was conducted on 798 students of the School of Public Health at the University of Warmia and Mazury in majors: nursing, midwifery, emergency medicine and dietetics (subgroup 1; n=428; 53.77%) and at the Faculty of Veterinary Medicine, major: veterinary medicine (subgroup 2; n=368; 46.23%). The study employed the diagnostic survey method using a questionnaire technique including Rosenberg's Self-Esteem Scale, MINI-COPE, PSS-10, and a selfquestionnaire. Results: The scores obtained by over half of the students were indicative of low global self-esteem, whereas over 80% of the students felt stress at a high intensity. Moreover, it was shown that the veterinary medicine students demonstrated a higher intensity of coping strategies, i.e. active coping (p<0.04) and planning (p<0.02), than medicine students. Conclusion: The study found that students experience a high level of stress regardless of the study major. The study revealed that students, irrespective of the major, experienced high levels of stress. Self-esteem had a significant impact on the stress level and methods of coping with difficult situations in students of medicine. A majority of the students applied positive styles of coping with stress.